Taiwan in world affairs (Westview Press, 1994)
Traditionally, Taiwan has been viewed as the passive pawn of more aggressive powers, yet now it has begun to assert its voice in world affairs - especially through economic influence. This volume brings together leading scholars, to examine the origins and implications of Taiwan's global role and the ramifications of its growing strength for such crucial policy issues as China's reunification and U.S. policy in East Asia.